Family Functioning, Family Structure, and Differentiation of Self in Heterosexual Spanish Couples: An Actor–Partner Analysis. - Rodríguez-González, Martiño; Schweer-Collins, Maria; Bell, Chance A.; Sandberg, Jonathan G.; Rodríguez-Naranjo, María Carmen (My University, 2019)
This study used an actor–partner interdependence model to assess the relationship between differentiation of self and family functioning in a sample of 118 heterosexual Spanish couples, with additional attention to family structural correlates, including age of the children, number of children in the household, and educational level. Results showed a significant actor effect, with greater differentiation of self levels predicting better family functioning within individuals. Implications for mental health professionals regarding differentiation are provided.
Keywords: Rol sexual; Pareja; Familia - Psicología; Family Assessment Device; Differentiation of self; Family functioning; Actor–partner interdependence modeling; Couples